Developing a Predictive Model of Crowd Behavior at Music Concerts and Festivals (MCF): A Proposal for a Research Framework - Cempaka Nur Huda Mohamad Halim; Masrur Mohd Khir; Azreen Roslan (Information Management and Business Review, 2024)
Music Concerts and Festivals (MCF) have experienced steady growth each year, transforming these events into large-scale international gatherings from their humble beginnings in the 1980s. The trend of increasing attendance by festival-goers and concert-goers at MCF has prominently emerged in the 21st century. The attendance of MCF contributes to the formation of crowds, which are indirectly influenced by risky behavior. Consequently, this trend has led to numerous incidents related to risky behavior at MCF. However, there is insufficient research on such behavior, and few existing studies address any predictive models specific to MCF. As a result, there has been a slight increase in aggressive behavioral incidents among festival-goers and concert-goers. This issue has demonstrated the importance of studying crowd behavior among those attending musical concerts and festivals. Therefore, this paper will focus on the important variables related to risky behavior that can cause crowd behavior and bridge the gap by identifying risky behavior among crowds. Additionally, this study will propose a research framework for the development of a crowd behavioral predictive model to anticipate future risk behavior among attendees. This research will employ a mixed-methods approach comprising both qualitative and quantitative methodologies as its method of investigation. The research framework will then be used to develop a predictive model of crowd behavior among attendees of MCF that will help to provide significant information for event and concert organizers to understand potential risky behavior among the crowd, hence, help in mitigating or preventing unwanted crowd safety incidents at MCF.